Nintendo : marketing strategies in a turbulent environment - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
This case study investigates the various positions that Nintendo has occupied in the global video games market, throughout the company's history. Readers are asked to consider the ways in which Nintendo has responded to changing market trends, and to evaluate how Nintendo might position itself as the market continues to evolve with the introduction of new gaming technologies.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Nintendo: Marketing Strategies in a Turbulent Environment. In International marketing (pp. 549-550). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Nintendo of America Inc; Marketing -- Case studies